Behavior of corner slab-column connections in irregular flat plate floors under gravity and bidirectional lateral loading - Soerya Widjaja (2010)
The structural behaviors of rectangular slab-column connections in modern flat plate structures are still unclear due to currently limited experimental data. One of the unclear aspects is the design value of transferred unbalanced moments, which are critical contributor to the connection shear stresses beside the gravity shear stresses. More accurate values of unbalanced moments can be obtained by modeling reduced slab stiffness due to slab cracking more accurately. However, currently available models do not represent the actual behavior of the cracked slab.